Association of urinary bisphenols and triclosan with thyroid function during early pregnancy. (December 2019) - Derakhshan, Arash; Shu, Huan; Peeters, Robin P.; Kortenkamp, Andreas; Lindh, Christian H.; Demeneix, Barbara; Bornehag, Carl-Gustaf; Korevaar, Tim I.M.
Abstract: Background: Bisphenols and triclosan are considered as potential thyroid disruptors. While mild alterations in maternal thyroid function can result in adverse pregnancy and child developmental outcomes, there is still uncertainty whether bisphenols or triclosan can interfere with thyroid function during pregnancy. Objectives: We aimed to investigate the association of urinary bisphenol A (BPA), bisphenol S (BPS), bisphenol F (BPF) and triclosan with early pregnancy thyroid function. Methods: This study was embedded in the Swedish Environmental Longitudinal, Mother and child, Asthma and allergy study (SELMA), a population-based prospective pregnancy cohort. In total, 1996 participants were included in the current study. Maternal urinary concentrations of three bisphenols and triclosan, collected at median (95% range) 10 (6–14) weeks of pregnancy as well as serum concentrations of thyroid stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3), total thyroxine (TT4), and total triiodothyronine (TT3) were measured. Results: Higher BPA levels were associated with lower TT4 concentrations (non-monotonic, P = 0.03), a lower FT4/FT3 ratio (β [SE] -0.02 [0.01], P = 0.03) and a lower TT4/TT3 ratio (β [SE] -0.73 [0.27], P = 0.008). Higher BPF levels were associated with a higher FT3 (β [SE] 0.01 [0.007], P = 0.04). There were no associations between other bisphenols or triclosan and absolute TSH, (F)T4 or (F)T3 concentrations. The association of BPA with thyroid function differed with gestational age. The negative association of BPA with FT4/FT3 and TT4/TT3 ratios was only apparent in early but not late gestation ( P for interaction: 0.003, 0.008, respectively). Conclusion: These human data during pregnancy substantiate experimental findings suggesting that BPA could potentially affect thyroid function and deiodinase activities in early gestation. Highlights: Bisphenol A (BPA) had a non-monotonic association with total T4 in pregnant women. Higher BPA was associated with lower (F)T4/(F)T3 ratio in very early pregnancy. Bisphenol F had a positive association with FT3. Bisphenol S and triclosan were not associated with thyroid function.